Trends in visits to a 24-hour walk-in crisis mental health centre during the COVID-19 pandemic - Lemoine, Jocelyne; Jiang, Depeng; Vakil, Tanvi; Bolton, James M.; Hensel, Jennifer M. (Frontiers in Health Services, 2025)
IntroductionThe sudden onset of the COVID-19 pandemic in the spring of 2020 introduced new stressors and exacerbated existing ones, which for many negatively impacted mental health or aggravated prior mental illness. As such, access to crisis care services was necessary and potentially increased, alongside public fears about virus contagion and stay-at-home public health orders. In Manitoba, Canada, visit rates were examined at a 24-hour mental health Crisis Response Centre (CRC) that offered in-person and virtual crisis assessments in a stepped care model during the COVID-19 pandemic.MethodsAll visits from the three years prior to the pandemic until September 28, 2022 were retrieved from the electronic patient record. Mean weekly visits had the pandemic not occurred were predicted with an autoregressive integrated moving average model and compared with observed rates.ResultsTotal pre-pandemic CRC visits (14,280) decreased 22.1%–11,122 total post-pandemic CRC visits. Visit rates remained lower than predicted throughout the observation period, with the total number of visits reduced by an average of 34.1 per week (p < .001) during the first pandemic wave, and that gap narrowing to an average of 18.9 visits per week (p = 0.001) during the fourth wave. Thirteen percent of pandemic visits were virtual; highest during the first wave (average of 34.1% of visits per week) and decreased to an average of 5.6% of visits per week during the last measured period.DiscussionFurther investigation is necessary to better understand this sustained pattern of reduced service utilization as we move beyond the pandemic.